2019
DOI: 10.1111/dom.13842
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic variability: The under‐recognized therapeutic target in type 1 diabetes care

Abstract: Type 1 diabetes mellitus (T1DM) remains one of the most challenging long‐term conditions to manage. Despite robust evidence to demonstrate that near normoglycaemia minimizes, but does not completely eliminate, the risk of complications, its achievement has proved almost impossible in a real‐world setting. HbA1c to date has been used as the gold standard marker of glucose control and has been shown to reflect directly the risk of diabetes complications. However, it has been recognized that HbA1c is a crude mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 97 publications
1
25
0
1
Order By: Relevance
“…8 This confirms hypoglycemia's major role on glycemic variability, an association to be considered in the context of the current debate on the link between these two glycemic disorders with the risk of vascular complications. 21,22 Despite an inverse relationship between TIR and HbA1c described in the literature (which we observed herein for both CGM devices, data not shown), the significant increase in FIG. 4.…”
Section: Discussionsupporting
confidence: 54%
“…8 This confirms hypoglycemia's major role on glycemic variability, an association to be considered in the context of the current debate on the link between these two glycemic disorders with the risk of vascular complications. 21,22 Despite an inverse relationship between TIR and HbA1c described in the literature (which we observed herein for both CGM devices, data not shown), the significant increase in FIG. 4.…”
Section: Discussionsupporting
confidence: 54%
“…Maintenance of GV within normal values is provided by a complex regulatory molecular-genetic network, which remains not fully understood. Many patients with diabetes have increased GV, which might be a major therapeutic challenge [ 1 , 2 ]. The highest GV is observed in insulin-treated type 1 and type 2 diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoglycemia is more common in individuals with increased GV [ 36 ]. A pooled analysis of six randomized controlled trials (RCTs) conducted among people with T2DM treated with 24 weeks of Gla-100 or comparators demonstrated that all measures of GV were significantly associated with poor glycemic control and the development of hypoglycemia during the trial [ 38 ]. Moreover, intraday GV is associated with a higher risk of nocturnal and overall hypoglycemia, and a decrease in GV is strongly correlated with a reduction in both hyperglycemic and hypoglycemic episodes [ 36 ].…”
Section: Recent Techniques For Measuring Blood Glucose Fluctuations: mentioning
confidence: 99%